Tb3+ and Eu3+ co-doped Ba6Bi9B79O138: color-tunable phosphors by utilizing the host-sensitization effect of Bi3+ and enhancement of red emission upon heating. (3rd February 2017) - Gao, Yan; Sun, Xiaorui; Feng, Zhongshan; Zhu, Liyue; Zhang, Jing; Gao, Wenliang; Zhou, Xianju; Cong, Rihong; Yang, Tao
Abstract : Color-tunable and white emissions were both achieved in Tb 3+ /Eu 3+ co-doped Ba6 Bi9 B79 O138 phosphors by utilizing the host-sensitization effect of Bi 3+ . Abstract : A series of Tb 3+ and Eu 3+ co-doped Ba6 Bi9 B79 O138 (BBBO ) phosphors were prepared by high-temperature solid-state reactions in order to utilize the host-sensitization effect of Bi 3+ . Energy transfer processes from Bi 3+ in the host to both Tb 3+ and Eu 3+, as well as from Tb 3+ to Eu 3+ were proved. Under UV-excitation, three emissions can be simultaneously observed in a single-phase phosphor, including a blue band attributed to Bi 3+ emission in the host, green lines due to Tb 3+ transitions of 5 D4 → 7 F J ( J = 6, 5, 4, 3), and red lines due to Eu 3+ transitions of 5 D0 → 7 F J ( J = 1, 2, 3, 4). Thus, the total emission could be rationally tuned by varying the relative doping contents of Tb 3+ /Eu 3+ and by selecting appropriate exciting irradiation. Thermal stability was investigated by in situ PL spectra at elevated temperatures. It is quite interesting to observe a significant enhancement of red emission in bothBBBO :0.05Eu 3+ andBBBO :0.05Tb 3+, 0.005Eu 3+ excited at 279 nm. Especially in the latter case, the red emission intensity at 150 °C is roughly 3 times that at room temperature, which is explained by the increasing efficiency of Bi 3+ → Eu 3+ and Tb 3+ → Eu 3+ energy transfer upon annealing.